From civil rights to human rights : Martin Luther King, Jr., and the struggle for economic justice - Jackson, Thomas F.; King, Martin Luther, Jr., 1929-1968. (Philadelphia, Pa. : University of Pennsylvania Press, 2007)
"Drawing widely on published and unpublished archival sources, Jackson explains the contexts and meanings of King's increasingly open call for "a radical redistribution of political and economic power" in American cities, the nation, and the world. The mid-1960s ghetto uprisings were in fact revolts against unemployment, powerlessness, police violence, and institutionalized racism, he argued. His final dream, a Poor People's March on Washington, aimed to mobilize Americans across racial and class lines to reverse a national cycle of urban conflict, political backlash, and policy retrenchment. King's vision of economic democracy and international human rights remains a powerful inspiration for those committed to ending racism and poverty in our time."--Jacket.
Introduction -- Pilgrimage to Christian socialism -- The least of these -- Seed time in the winter of reaction -- The American Gandhi and direct action -- The dreams of the masses -- Jobs and freedom -- Malignant kinship -- The secret heart of America -- The war on poverty and the democratic socialist dream -- Egyptland -- The world house -- Power to poor people.
Includes bibliographical references (pages 425-437) and index.
Liberty Legacy Foundation Award, 2007
Keywords: King, Martin Luther, -- Jr., -- 1929-1968.; King, Martin Luther, -- Jr., -- 1929-1968.; King, Martin Luther -- 1929-1968; King, Martin Luther, -- Jr., -- 1929-1968.; King, Martin Luther; g; Human rights -- United States; African Americans -- Civil rights; African Americans -- Civil rights; Human rights; Schwarze; 2; Wirtschaftliche Lage; Human rights -- United States; African Americans -- Civil rights; United States; USA; Schwarze